An Evaluation of Illicit Stimulants and Metabolites in Wastewa ter Effluent and the Wisconsin River Along the Central Wisconsin River Basin - Erik S. Hendrickson; Isaiah J. Robertson (Acta Scientiarum Polonorum. Formatio Circumiectus)
The goals of the study were to develop a method for extracting and quantifying illicit stimulants and metabolites, methamphetamine, amphetamine, cocaine, and benzoylecogonine from wastewater effluent and surface water grab samples, and evaluate Central Wisconsin wastewater treatment plant’s (WWTP) removal efficiency of compounds of interest. The method created used HLB solid-phase extraction (SPE) cartridges to extract substances of interest and High Performance Liquid Chromatography tandem Mass Spectrometry (HPLC/MS/MS) for quantification and qualification. All four wastewater effluent samples and three Wisconsin River samples had quantifiable concentrations of at least one analyte. Conclusions derived from the study were: The method created is effective for separating, quantifying, and identifying amphetamine, cocaine, and benzoylecognine from wastewater effluent and surface water grab samples, and each illicit stimulant and metabolite analyzed in this study were all quantified in wastewater effluent, indicating these compounds have the ability to survive WWTP.